O processo de transição escola-trabalho no Brasil: primeiro emprego, emprego decente e heterogeneidades nacionais em perspectivas comparativas - Stélio Coêlho Lombardi Filho (2019)
This thesis sought to deepen the understanding of an important aspect of youth labor market dynamics, the school-to-work transitionprocess, in a context of demographic changes.The study aims to shed light on the impact of sociodemographic,generational and economic cycle elements on the movement of leavingschool and entering the labor market, seekingalsoto verify gender discrepancies and national heterogeneities through comparisons between the Brazilian reality andthatfrom other Latin American countries. To this end, three empirical exercises were performed to clarify relevant questions about the school-to-work transition. The findings of the first essay, which aimed to understand how demographic changes have influenced young people's occupational choices, make it clear thatat least since the late 1980s, changes in demand for education and family dynamics have been causing significant changes in study, work and job search decisions by this age group. Indeed, there has been a greater demand for educational qualifications and a propensity to combine study and work, which tends to postpone some stages of the transition to adulthood. In addition, there is a strong gender component present in the process, especiallythe effects that the educational transition has had on women's positions. The results show that structural transformations are acting more intensively towards their activation in the labor market, although the rates ofNEETyoungwomen are still high. Then, the second application ofthis thesis sought to identify the determinants of the youth’s occupationalconditiontransition, aiming to understand the variations between periods of the effects of socioeconomic and demographic factors on the transition probabilities. The results of this stage pointed to the existence of significant differences of gender and race in the transition patterns, with the permanence in unemploymentbeinggreater for black women, as well as the transition to inactivity. Regarding the educational level of young people, more years of study were associated with greater activation in the labor market, but with effects that vary by sex and over time. Moreover, asexpectedin a stratified and highly unequal society such asthe onein Brazil, income is a crucial element in explaining transition patterns. As income levels rise, the chances that young people of both sexes will make the ocupied-ocupiedtransitiongrows further. Finally, the third and final xixapplication of the Thesis had two main objectives: to include the qualitative aspect in the discussion about school-to-work transition and to carry out comparative analyzes between Brazil, Peru and Colombia. It can be said that there are important heterogeneities betweenthesecountries regarding the effects of sociodemographic characteristics on the quality of the school-to-work transition. And while there is a higher proportion of men than women who have completed thistransition in all countries analyzed, this difference is greater in Brazil.